Novel Method for an Optimised Calculation of the Cross-Sectional Distribution of Live Loads on Girder Bridge Decks - Alvaro Gaute-Alonso; David Garcia-Sanchez; Iñigo Calderon Uriszar-Aldaca; Claudio Lopez Castillo (Salehan Institute of Higher Education, 2022)
One of the main goals in the design of girder bridge deck systems is to determine the cross-sectional distribution of live loads across the different girders that make up the cross-section of the deck. Structural grillage models and current bridge design standards based on a Load Distribution Factor (LDF) provide oversized designs, as demonstrated in this paper. This research introduces a novel method that allows the cross-sectional distribution of live loads on girder bridge decks to be calculated by applying a matrix formulation that reduces the structural problem to 2 degrees of freedom for each girder: the deflection and the rotation of the deck-slab at the centre of the girder’s span. Subsequently, a parametric study is presented that analyses the structural response of 64 girder bridge decks to a total of 384 load states. In addition, the authors compare the outputs of the novel method with those obtained using traditional grillage calculation methods. Finally, the method is experimentally validated on two levels: a) a laboratory test that analyses the structural response of a small-scale girder bridge deck to the application of different load states; b) a real full-scale girder bridge load test that analyses the structural response of the bridge over the Barbate River during its static load test. Based on this analysis, the maximum divergence of the proposed method obtained from the experimental structural response is less than 10%. The use of the proposed novel analysis method undoubtedly provides significant savings in material resources and computing time, while contributing to minimizing overall costs. Doi: 10.28991/CEJ-2022-08-03-01 Full Text: PDF